Axillary Surgery in Breast Cancer Patients Treated with Breast-Conserving Surgery at German Breast Cancer Centers Within the Last 14 Years – Comparison of a University Center and a Community Hospital - de Gregorio, Amelie; Widschwendter, Peter; Albrecht, Susanne; de Gregorio, Nikolaus; Friedl, Thomas W. P.; Huober, Jens; Janni, Wolfgang; Ebner, Florian K. (Geburtshilfe und Frauenheilkunde, 2018)
Background Guideline recommendations for axillary surgical approach in breast cancer (BC) treatment changed over the last decade.Methods Data from all invasive BC patients (n = 5344) treated with breast conserving surgery (BCS) at the breast cancer centers of the University Hospital Ulm (U-BCC) and the community hospital Dachau (D-BCC) were included into a retrospective analysis for assessing information on axillary surgery between 2003 and 2016 based on the documented cancer registry data.Results The average annual rate of sentinel node biopsy (SNB) was 85.5% and 87.2% in Ulm and Dachau, respectively. SNB was performed more precisely at the U-BCC with a median of 2.4 resected lymph nodes (LN) compared to a median of 3.2 resected LN in Dachau. Median number of resected LN for axillary lymph node dissection (ALNE) showed a statistically significant reduction over time in Ulm (rs = − 0.82; p < 0.001) and Dachau (rs = − 0.76; p = 0.002). The rate of secondary ALNE (after SNB; 2° ALNE) decreased significantly in U-BCC (rs = − 0.76; p = 0.002) while it remained stable in D-BCC. The influential publication of the Z0011 study in 2010 resulted in a significant reduction of secondary ALNE (24.1% preZ0011 and 14.4% postZ0011; p < 0.001) in Ulm.Conclusion Changes in axillary surgery over time can be seen in the annual statistics of the reviewed BCCs. With BCS, mostly SNB was performed and numbers of removed LN in ALNE have decreased. In the U-BCC, the rate of 2° ALNE dropped after the publication of the Z0011 data. The fact that no such decrease for 2° ALNE was found in D-BCC suggests that university hospitals implement new data and research results into clinical routine earlier than peripheral community hospitals.
Keywords: breast cancer; national guidelines; treatment changes; sentinel node biopsy; axillary lymph node dissection